Effects of Exposure Duration to Cottonseed Cake-Based Diets on Broiler Performance - Adeyemo, G.O. (International Journal of Poultry Science, 2010)
Two experiments were separately conducted using cottonseed cake-based diets to feed table birds. In the first experiment (phase 1) broiler birds were fed from day old to 8 weeks of age, while in the second experiment (phase 2), the birds were fed cottonseed cake based diets from 4-8 weeks of age. Five dietary treatments were fed in both experiments formulated to be iso-caloric and iso-nitrogenous with Cottonseed Cake (CSC) replacing Soyabean Cake (SBC) at 0, 25, 50, 75 and 100% respectively. The live weight of broilers in the phases differed significantly (p<0.05) with broilers in phase 2 being better. The dressed weight was higher in phase 2 than phase 1. Broilers fed CSC based diets from 4 weeks had better feed conversion ratio than those fed from day old. Similar trend was observed in haematological and serum biochemistry parameters in the different treatments of the two phases. It can be concluded that feeding CSC protein as replacement for SBC protein was better from 4 weeks of age in respect of broiler performance though at a higher cost than the former.